PERKEMBANGAN WACANA IDENTITAS ARSITEKTUR DALAM JURNAL-JURNAL ARSITEKTUR DI AWAL ABAD XX DI HINDIA BELANDA - Mahatmanto (Jurnal Koridor, 2018)
The transition of the 19th century to the 20th century known as the flowering period of the printed mass media in the West and the colonies. Similarly, in the Dutch East Indies, in the turn of the century, many publications are created, written and read by the architects who come to enjoy this print technology development in order to always be able to follow the progress in the Netherlands. At the turn of the century it was known four publications that circulated among architects in the Indies. Ideologies and interests with each of them carrying, mixing, and developed the ideas of architecture are increasingly different from the original. This process is in line with the development of the ideas of nationalism in a society that demands the assertion of identity in the form of nation-state nation Indonesia. This study surveyed the development of the contents of the four publications related to architecture in the Dutch East Indies, which is the method of Discourse Analysis, found patterns of discourse that lies behind the development of architectural identity discourse in the aftermath of Indonesia's independence.